Effect of post-annealing on cation substituted kesterite solar cells - Susilo, Richardus (Nanyang Technological University, 2020)
Kesterite Cu2ZnSnS4 (CZTS) is a cost-efficient, environmentally friendly, and stable photovoltaic material comprising of earth-abundant elements. However, the record power conversion efficiency for such solar cells has been stagnant mainly due to high VOC deficit. The primary cause of the large VOC deficit is non-radiative recombination within the heterojunction region. Heat treatment (post-annealing) is one of the ways to reduce heterojunction recombination. This report focuses on the effect of post-annealing temperature, duration, and post-annealing step (that is, post-annealing after CdS deposition or after ITO deposition) on the IV and EQE characteristics of kesterite solar cells. The concept of double post-annealing is also explored, which is the first study in this research field. EQE results suggest increased light absorption for post-annealed samples, specifically in the mid-wavelength region (500-800 nm). Moreover, post-annealing after ITO further increases the light absorption in the low wavelength region (< 400 nm). IV characteristics shows the optimum temperature for post annealing temperature after ITO and CdS are 270 oC and 315 oC respectively. Highest efficiency of 10.2 % was observed for sample post-annealed after CdS at 315 oC for 5 minutes. On the other hand, double post-annealing provides no improvement in solar cell performance compared to single post-annealing.